Structural and physical properties of trilayer nickelatesR4Ni3O10(R=La, Pr, and Nd) - Rout, Dibyata; Mudi, Sanchayeta Ranajit; Hoffmann, Marco; Spachmann, Sven; Klingeler, Rüdiger; Singh, Surjit (Physical review, 2020)
We investigate in detail the low-temperature structural and physical properties of the trilayer nickelates R4Ni3O10 (R=La, Pr, and Nd), which crystallize with a monoclinic symmetry (space group P21a,Z=4) and undergo a metal-to-metal transition (MMT) near TMMT= 135K(La), 156K (Pr), and 160K (Nd). Using a high-resolution synchrotron powder x-ray diffraction technique, we show that the lattice parameters in all cases exhibit an anomalous behavior at TMMT, however, without any sign of change in the lattice symmetry. Unambiguous signature of MMT is also observed in the magnetic and transport data, suggesting a strong coupling between the electronic, magnetic, and structural degrees of freedom. Analysis of thermal expansion yields hydrostatic pressure dependence of MMT in close agreement with previous high-pressure experiments. In Pr4Ni3O10, the Pr3+ ions located in the rocksalt (RS) layers order magnetically near 5K, which is significantly suppressed compared to θp∼−36K. In contrast, Pr3+ ions in the perovskite-block (PB) layers exhibit a crystal field (CF) induced nonmagnetic singlet ground state. In Nd4Ni3O10, on the other hand, the CF ground state of Nd3+ ions in both RS and PB layers is a Kramers doublet. The heat capacity of Nd4Ni3O10 shows a pronounced Schottky-like anomaly near 40K, and a sharp upturn indicating short-range correlations between the Nd-moments below 10K. However, no signs of long-range ordering of Nd-moments could be found down to 2K despite a sizable value of θp∼−40K. The strongly suppressed magnetic long-range ordering in both R=Pr and Nd suggests the presence of strong magnetic frustration in these compounds. In the presence of an overwhelming Schottky contribution, the electronic term in the specific heat of Pr4Ni3O10 and Nd4Ni3O10 appears highly inflated, which can be falsely interpreted as a sign of heavy fermion behavior as is done in a recent study on Nd4Ni3O10. Accordingly, the low-temperature resistivity of these compounds is found to follow a −T0.5 rather than a −lnT dependence.
In Titel die Zahlen 4, 3 und 10 sind tiefgestellt
Gesehen am 21.12.2020